A Study on Recyclability of Alsi7mg0.3 Machining Waste - Gökelma, Mertol; Gökelma, Mertol; Önen Tüzgel, Rabia; Kaya, Ahmet Yiğit; Özaydın, Onur (My University, 2023)
Aluminium products are widely used in the automotive industry. One of the important aluminium products in the automotive is wheel production. Turkish wheel production is expected to reach 360000 tons in 2025. The wheels are produced by Low-Pressure Die Casting at the first stage and the machining process in CNC machines is used to create the final form. A significant amount of machining waste (swarf, turnings, and chips) is created during the machining and the importance of secondary aluminium has been increasing due to environmental and economic concerns. This study focuses on the recycling of AlSi7Mg0.3 cast alloy machining waste. The turnings were sorted into two size fractions and remelted separately under a salt flux in a resistance heating furnace. Two different salt mixtures with different melting points and different salt factors were studied in this work. Metal yield and coagulation yield after remelting were discussed.